2009
DOI: 10.1002/lary.20084
|View full text |Cite
|
Sign up to set email alerts
|

Dural arteriovenous fistula: Diagnosis, treatment, and outcomes

Abstract: A DAVF is a vascular lesion that is best diagnosed with conventional angiography, but can often be found with MRA. Treatment with endovascular embolization is effective and has few significant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 13 publications
0
24
1
Order By: Relevance
“…The discrepancy between the current results and the findings of Cohen et al, 21 however, does require further discussion. In that series of 46 patients, 13 patients underwent CTA, only 2 of whom had findings positive for DAVF.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…The discrepancy between the current results and the findings of Cohen et al, 21 however, does require further discussion. In that series of 46 patients, 13 patients underwent CTA, only 2 of whom had findings positive for DAVF.…”
Section: Discussioncontrasting
confidence: 97%
“…21,28,29 Studies have used a variety of techniques and sequences and have shown variable diagnostic performance. De Marco et al 28 presented some of the earliest data, finding MR imaging cortical vein dilation and venous occlusion in 8 of 12 patients with angiographically proved DAVF by using basic spin-and gradient-echo sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 Studies have reported, however, that CTA has reduced sensitivity versus MRA for the detection of DAVFs (15.4% versus 50%). 37 Time-resolved MRA techniques are also promising and may be reliable for DAVF screening and surveillance in the future. 38,39 Due to current limitations of low resolution, restricted FOV, and saturation artifacts, the negative predictive value of MRA is inadequate to exclude DAVFs.…”
Section: Diagnosismentioning
confidence: 99%